2019
DOI: 10.1016/j.surfcoat.2018.12.100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bias voltage on the tribological and sealing properties of rubber seals modified by DLC films

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Diamond-like carbon (DLC) films have garnered considerable interest as materials for lubrication and protection, due to the combination of relatively high hardness, ultralow friction, and excellent wear resistance [7][8][9]. Beyond that, DLC films not only possess promising chemical compatibility with the rubber (to prevent the degradation of rubber components) but the deposition temperature can be adjusted to be lower than the upper temperature limit of the rubber (by the choice of the deposition method and controlling process variables) [10][11][12][13]. Therefore, DLC films prepared on the rubber surface is undoubtedly a viable option.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond-like carbon (DLC) films have garnered considerable interest as materials for lubrication and protection, due to the combination of relatively high hardness, ultralow friction, and excellent wear resistance [7][8][9]. Beyond that, DLC films not only possess promising chemical compatibility with the rubber (to prevent the degradation of rubber components) but the deposition temperature can be adjusted to be lower than the upper temperature limit of the rubber (by the choice of the deposition method and controlling process variables) [10][11][12][13]. Therefore, DLC films prepared on the rubber surface is undoubtedly a viable option.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, the surface morphology of DLC films in the form of "hills" tends to have higher roughness compared to virgin NBR. Noteworthy, Liu et al [35,36] reported that the fabrication of the DLC film is beneficial to lower the surface roughness of NBR. Our results are contrary to previous study, which may be related to the thickness of films, the distribution and size of the depressions on rubber, and the effect of Ar plasma pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…, the low hardness of films may have direct relation with tribological behaviors. It was reported that amorphous carbon film with high hardness on rubber would have better wear resistance [36]. The increasingly hydrogenated CH 4 gas discharge plasma promotes the formation of the graphite phase (Table 1), thereby reducing the hardness of the film and impairing the load capacity of the hydrocarbon network.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of DLC films, their application as a selflubricating and protective coating in mechanical engineering is increasingly broadened. For example, their applications in gearings (Michalczewski et al, 2019), bearings (Okamura et al, 2019), engine piston rings (Kumar et al, 2019), oil-well tubings , rubber seals (Liu J. Q. et al, 2019), and friction pairs in spacecraft (Donnet et al, 1999) have been testified to be effective and valuable. Superlubricity achieved with DLC coatings can provide a new concept to meet the increasing demand for lower energy consumption, longer life time, and higher power density of future mechanical systems, which has an enormous potential value from both economic and environmental perspectives.…”
Section: Discussionmentioning
confidence: 99%